PERCEPTIONS OF PREGNANT WOMEN ABOUT DENTAL PRENATAL CARE - Martins Mesquita, Lívia Karynne (2022)
This study aimed to analyze the perceptions of pregnant women about dental prenatal care in a city in northeastern Brazil. It was a qualitative research conducted in Crateús, Ceará, from June 2020 to February 2021, at the Maratoan Family Health Unit. Data collection occurred through semi-structured interviews with 12 pregnant women. The empirical material developed was transcribed and analyzed using the thematic content analysis technique. The following thematic categories emerged: Self-perception of pregnant women about the importance of dental prenatal care; Access flows to dental prenatal care; Dental phobia or trauma. Participants recognized the importance of prenatal dental care, but not so sure why. Dental care during pregnancy is permeated with myths and mistrust, and the lack of bonding between the health team and patients is one of the factors that most keep pregnant women away from the dentist. Qualified listening by the dentist in dental prenatal care can demystify possible fears and traumas of pregnant women and encourage the creation and strengthening of professional-patient relationship. There is need to invest in health education, with pregnant women as protagonists of their own care, supported by professional care practices developed in dynamic, interactive, and multidisciplinary groups.